2018
DOI: 10.1016/j.apergo.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing experience in crowds – The organiser perspective

Abstract: Crowds are a commonplace encounter but the experience for participants can be highly variable. Crowds are complex sociotechnical phenomenon, affected by many interacting factors. Little is known, however, about how those responsible for organising crowd situations approach their responsibilities. This study conducted semi-structured interviews (n = 41) with organisers responsible for different aspects of the design, planning, management and operations of events and other crowd situations. The objective was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…street or field festivals). In a wider examination of the activities of crowd organisers, Filingeri et al [5] found that organisers tended to rely on experience and judgement in approaching their planning and decisions, without accessing training or the guidance materials available. The organisers of infrequent or small-scale events can have the greatest knowledge and experience gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…street or field festivals). In a wider examination of the activities of crowd organisers, Filingeri et al [5] found that organisers tended to rely on experience and judgement in approaching their planning and decisions, without accessing training or the guidance materials available. The organisers of infrequent or small-scale events can have the greatest knowledge and experience gap.…”
Section: Discussionmentioning
confidence: 99%
“…Filingeri et al [4,5] reported the findings of interview and observations studies of multiple crowd situations, which examined the factors affecting crowd participant experience. This paper presents further analysis of the data from these studies, focusing on risk and management of STF in crowd situations.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental advertising should particularly be exercised through social media, as it commands the greatest reach and it is a key part in brand development and loyalty (Hudson et al , 2015). However, it is important to understand and consider the attitudes that audiences will bring with them to the festival to develop an effective sustainable social media marketing plan for sustainability (Brennan et al , 2019; Jackson et al , 2014) and consider more factors that can affect the positive experience of participants (Filingeri et al , 2018). The use (or lack of) environmental advertising and proper environmental facilities can directly impact the level of engagement of pro-environmental behaviour of patrons at music festivals (Alonso-Vazquez, 2015).…”
Section: The Consumption Patterns Of Patronsmentioning
confidence: 99%
“…Introduction: The Constraints of Event Crowd Management Ali-Knight (2007, 2011) and Robertson and Rogers (2009) observed from in-depth interview data with event directors in the UK that there is much evidence that organizational priorities and creative capacity is often limited by external pressures (e.g., media, finance or funding, and policy or politics). In their review of factors influencing the experience of crowds at events in the UK, Filingeri, Eason, Waterson, and Haslam (2018) interviewed a range of event organizers responsible for crowd management (N = 41) in the UK. The results indicated that the priorities of finance, security, health, and safety determined a crowd management process that was about reducing liability (Abbott & Geddie, 2000;Reid & Ritchie, 2011), "rather than enhancing satisfaction" (Filingeri et al, 2018, p. 18).…”
Section: Robertson Hutton and Brownmentioning
confidence: 99%
“…In essence, an understanding of the psychosocial domain must contribute to the civic responsibility of making lives better. Crowd management as applied to most mass events is, as Filingeri et al (2018) observed, based on behaviorist models that don't allow for more complex involvement in experience or efforts to build social trust.…”
Section: Turbulent Times and Transformationmentioning
confidence: 99%